2018
DOI: 10.1038/s41598-018-34345-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase-delta could be a biomarker for eosinophilic nasal polyps

Abstract: Nasal polyps (NP) cause diverse clinical symptoms of chronic rhinosinusitis (CRS). Chronic inflammation of sinonasal mucosa is known to be crucial in NP formation. We aimed to define the implications of phosphoinositide 3-kinase (PI3K)-δ in nasal inflammation associated with NP by analyzing NP tissue obtained from CRS patients. Results showed that expression of p110δ, a regulatory subunit of PI3K-δ, in NP tissue was increased compared to control tissue. Increased p110δ expression was closely correlated with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Kim et al found that PI3k-110δ was increased in eCRSwNP. 9 In this study, we used the eCRSwNP mouse model, PI3K/Akt/mTOR pathway inhibitors, and autophagy inhibitors and activators to investigate the regulatory effects of the PI3K/Akt/mTOR pathway on autophagy, and their effects on eosinophilic inflammation, and tissue remodeling. The role of type 2 innate lymphoid cells (ILC2s) in eCRSwNP was also studied, and the relationship between ILC2s and autophagy was preliminarily determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al found that PI3k-110δ was increased in eCRSwNP. 9 In this study, we used the eCRSwNP mouse model, PI3K/Akt/mTOR pathway inhibitors, and autophagy inhibitors and activators to investigate the regulatory effects of the PI3K/Akt/mTOR pathway on autophagy, and their effects on eosinophilic inflammation, and tissue remodeling. The role of type 2 innate lymphoid cells (ILC2s) in eCRSwNP was also studied, and the relationship between ILC2s and autophagy was preliminarily determined.…”
Section: Introductionmentioning
confidence: 99%
“…Class Ⅲ PI3K and mTOR complex 1 (mTORC1) in the PI3K/Akt/mTOR pathway can regulate autophagy 8 ; however, the PI3K/Akt/mTOR pathway has rarely been studied in eCRSwNP and its role remains unclear. Kim et al found that PI3k‐110δ was increased in eCRSwNP 9 …”
Section: Introductionmentioning
confidence: 99%